Media Interaktif Pengenalan Karakter Wayang Pandawa, Metode Talking Stick Pada Siswa Kelas III SD Negeri Jatisari Semarang - Erria Dilasetiara; Fitro Nur Hakim (Jurnal Informatika Upgris, 2018)
Based on the results of observation, the learning method used in SD N Jatisari Semarang is in the form of discourse, discussions, question and answer with the book media. Learning methods that have been applied so far have not had enough impact on students' level of understanding. The method used is less successful, so students feel bored and bored. This study uses the concept of interactive media, the "Talking Stick" method, develops interactive systems and brings interesting features, through historic wayang characters. The advantage of this media is to modify recognition of wayang products through digital services on computer-based systems that respond to user actions, another advantage is that teachers can change evaluation questions. The results of the students' scores before using the learning media, on average 41% - 60% including the meanings were quite low, while after using the media were 81% - 100% including very high.